Optical fiber and optical fiber preform

CN117581128BActive Publication Date: 2026-10-27SUMITOMO ELECTRIC INDUSTRIES LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202280041861.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2021-07-16
Filing Date
2022-06-29
Publication Date
2026-10-27
Estimated Expiration
2042-06-29

AI Technical Summary

Technical Problem

由此,产生来自玻璃缺陷的传输损耗增加

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117581128B_ABST
    Figure CN117581128B_ABST
Patent Text Reader

Abstract

An optical fiber is composed of a silica-based glass. The optical fiber has a core and a cladding that circumscribes the core. The core has a first core that includes a central axis and a second core that circumscribes the first core. An average value of a mass fraction of chlorine in the first core is lower than an average value of a mass fraction of chlorine in the second core. An average value of a mass fraction of fluorine in the first core is higher than an average value of a mass fraction of fluorine in the second core. A total value of the average value of the mass fraction of chlorine and the average value of the mass fraction of fluorine in the second core is 5000 ppm or less. The core contains either or both of an alkali metal element and an alkaline earth metal element.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This disclosure relates to optical fibers and optical fiber preforms. This application claims priority based on Japanese Application No. 2021-117840, filed on July 16, 2021, and invokes all the contents set forth in that Japanese application. Background Technology

[0002] Typically, when the core of silica-based glass contains alkali metals or alkaline earth metals, the core viscosity decreases during fiber drawing to manufacture optical fibers, and the glass rearrangement is promoted, thus reducing transmission loss caused by Rayleigh scattering in the optical fiber. Hereinafter, alkali metals and alkaline earth metals will be referred to as the "alkali metal group".

[0003] In the absence of chlorine in the core containing alkali metal elements, or with a low chlorine content, the alkali metal elements added to the center of the core in the form of the fiber matrix diffuse during fiber drawing. This breaks the bonds in the glass molecular structure, creating glass defects. Consequently, transmission loss increases due to these glass defects. When the core contains a sufficient amount of chlorine, the alkali metal elements bind to the glass defects through the chlorine. This suppresses the formation of glass defects, reducing the increase in transmission loss from them.

[0004] To reduce the increase in transmission loss due to glass defects, the optical fibers disclosed in Patent Documents 1 and 2 contain chlorine in their core, in addition to the alkali metal element group. In the optical fibers disclosed in Patent Documents 1 and 2, when the core is divided into an inner core and an outer core, the chlorine concentration in the inner core is lower than that in the outer core. Thus, by reducing the chlorine concentration in the inner core containing the alkali metal element group, defects such as crystallization occurring during preforming are reduced. Furthermore, it is believed that by increasing the chlorine concentration in the outer core, glass defects caused by the diffusion of the alkali metal element group during fiber drawing can be repaired, thereby suppressing the increase in transmission loss due to glass defects.

[0005] Existing technical documents

[0006] Patent documents

[0007] Patent Document 1: Japanese Patent Publication No. 2009-541796

[0008] Patent Document 2: Japanese Patent Application Publication No. 2017-76053

[0009] Patent Document 3: Japanese Patent Application Publication No. 2019-191297 Summary of the Invention

[0010] One embodiment of this disclosure relates to an optical fiber made of silica-based glass, comprising: a core and a cladding circumscribed around the core, wherein the refractive index of the core is greater than that of the cladding, the core having a first core including a central axis and a second core circumscribed around the first core, wherein the average mass fraction of chlorine in the first core is lower than the average mass fraction of chlorine in the second core, the average mass fraction of fluorine in the first core is higher than the average mass fraction of fluorine in the second core, the sum of the average mass fraction of chlorine and the average mass fraction of fluorine in the second core is 5000 ppm or less, and the core contains any one or both of alkali metal elements and alkaline earth metal elements.

[0011] One embodiment of this disclosure relates to an optical fiber preform comprising: a core and a cladding portion externally connected to the core, wherein the refractive index of the core is greater than that of the cladding portion, the core having a first core including a central axis and a second core externally connected to the first core, wherein the average mass fraction of chlorine in the first core is lower than the average mass fraction of chlorine in the second core, the average mass fraction of fluorine in the first core is higher than the average mass fraction of fluorine in the second core, and the combined average mass fraction of chlorine and fluorine in the second core is 5000 ppm or less, and the core contains any one or both of alkali metal elements and alkaline earth metal elements. Attached Figure Description

[0012] [ Figure 1 ] Figure 1 This is a cross-sectional view of the optical fiber involved in the implementation method.

[0013] [ Figure 2 ] Figure 2 This is a flowchart illustrating a method for manufacturing an optical fiber according to an embodiment.

[0014] [ Figure 3 ] Figure 3 This is a graph showing the relationship between the average mass fraction of chlorine and the sum of the average mass fraction of fluorine in the second core and the transmission loss.

[0015] [ Figure 4 ] Figure 4 This is a graph showing the relationship between the difference between the average fluorine concentration of the cladding and the average fluorine concentration of the second core and the transmission loss.

[0016] [ Figure 5 ] Figure 5 This is a graph showing the relationship between the average mass fraction of chlorine in the second core and transmission loss.

[0017] [ Figure 6 ] Figure 6 This is a graph showing the relationship between the average potassium concentration in the core and transmission loss. Detailed Implementation

[0018] [The problem this disclosure aims to solve]

[0019] In the optical fibers disclosed in Patent Documents 1 and 2, the reduction in transmission loss is insufficient due to the low chlorine concentration in the inner core. In the optical fibers disclosed in Patent Documents 1 and 2, the reduction in transmission loss is insufficient, depending on the halogen concentrations of the inner and outer cores.

[0020] The purpose of this disclosure is to provide optical fibers and optical fiber preforms that balance manufacturability and reduced transmission loss.

[0021] [The Effects of This Disclosure]

[0022] According to this disclosure, it is possible to provide optical fibers and optical fiber preforms that balance manufacturability and reduced transmission loss.

[0023] [Description of embodiments of this disclosure]

[0024] First, embodiments of this disclosure are listed and described. The optical fiber involved in the embodiments of this disclosure is an optical fiber made of silica-based glass, comprising: a core, and a cladding circumscribed around the core. The refractive index of the core is greater than that of the cladding. The core has a first core including a central axis and a second core circumscribed around the first core. The average mass fraction of chlorine in the first core (hereinafter referred to as average chlorine concentration) is lower than the average chlorine concentration of the second core, and the average mass fraction of fluorine in the first core (hereinafter referred to as average fluorine concentration) is higher than the average fluorine concentration of the second core. The combined average chlorine concentration and average fluorine concentration of the second core are 5000 ppm or less. The core contains any one or both of alkali metal elements and alkaline earth metal elements. For example, when the average chlorine concentration is 2000 ppm and the average fluorine concentration is 2000 ppm, the combined average chlorine concentration and average fluorine concentration is 4000 ppm.

[0025] In the aforementioned optical fibers, both manufacturability and transmission loss can be reduced.

[0026] The average chlorine concentration of the first core can be between 10 ppm and 500 ppm. Under these conditions, manufacturability and reduced transmission losses can be easily balanced. When the average chlorine concentration of the first core is less than 10 ppm, insufficient chlorine combines with glass defects generated during drawing, leading to increased transmission losses. When the average chlorine concentration of the first core exceeds 500 ppm, base material defects may sometimes occur during base material manufacturing due to reactions with alkali metal elements.

[0027] The average chlorine concentration of the second core can be between 500 ppm and 3000 ppm. In this case, manufacturability and reduced transmission losses can be easily balanced. When the average chlorine concentration of the second core is less than 500 ppm, insufficient chlorine combines with glass defects generated during drawing, leading to increased transmission losses. When the average chlorine concentration of the second core exceeds 3000 ppm, even though the second core does not contain alkali metal elements in the base material stage, it may sometimes react with alkali metal elements due to diffusion during base material manufacturing, resulting in base material defects.

[0028] The average fluorine concentration of the first core can be between 500 ppm and 4000 ppm. In this case, manufacturability and reduced transmission loss can be easily balanced. When the average fluorine concentration of the first core is below 500 ppm, the reduction in Rayleigh scattering loss due to decreased viscosity is insufficient, leading to increased transmission loss. When the average fluorine concentration of the first core exceeds 4000 ppm, transmission loss increases due to concentration fluctuations.

[0029] The average fluorine concentration of the second core can be between 500 ppm and 4000 ppm. In this case, manufacturability and reduced transmission loss can be easily balanced. When the average fluorine concentration of the second core is below 500 ppm, the reduction in Rayleigh scattering loss due to decreased viscosity is insufficient, leading to increased transmission loss. When the average fluorine concentration of the second core exceeds 4000 ppm, transmission loss increases due to concentration fluctuations. By adding fluorine to the second core, the core viscosity is reduced compared to the case of chlorine alone, thereby reducing transmission loss caused by Rayleigh scattering.

[0030] The average combined mass fraction of alkali metals and alkaline earth metals in the core (hereinafter referred to as the average concentration) can be between 0.2 ppm and 200 ppm. Under these conditions, both manufacturability and reduced transmission loss can be easily achieved. When the average concentration is below 0.2 ppm, the reduction in Rayleigh scattering loss due to decreased viscosity is insufficient, leading to increased transmission loss. When the average concentration exceeds 200 ppm, transmission loss increases due to concentration fluctuations.

[0031] The average concentration of alkali metals and alkaline earth metals in the core can be above 30 ppm. Under these conditions, it is easier to balance manufacturability and reduced transmission losses.

[0032] The core can contain any one of sodium, potassium, rubidium, cesium, or calcium as an alkali metal or alkaline earth metal. In this case, transmission loss can be easily reduced.

[0033] In the optical fiber of this disclosure, which sufficiently reduces transmission loss, the transmission loss does not deteriorate even under radiation. That is, transmission loss can be reduced even if the optical fiber does not have an OD matrix. Such transmission loss can be reduced by suppressing glass defects under high chlorine concentrations.

[0034] The difference between the average mass fraction of fluorine in the cladding and the average mass fraction of fluorine in the second core can be above 8400 ppm. In this case, transmission loss can be further reduced.

[0035] The difference between the average mass fraction of fluorine in the cladding and the average mass fraction of fluorine in the second core can be between 8600 ppm and 9000 ppm. In this case, transmission loss can be further reduced.

[0036] The average mass fraction of fluorine in the cladding can be between 8000 ppm and 13000 ppm. In this case, transmission losses can be further reduced.

[0037] The optical fiber parent material disclosed herein comprises: a core and a cladding portion externally connected to the core, wherein the refractive index of the core is greater than that of the cladding portion, the core having a first core including a central axis and a second core externally connected to the first core, wherein the average chlorine concentration of the first core is lower than that of the second core, the average fluorine concentration of the first core is higher than that of the second core, the combined average chlorine concentration and average fluorine concentration of the second core is 5000 ppm or less, and the core contains any one or both of alkali metal elements and alkaline earth metal elements.

[0038] Among the aforementioned optical fiber parent materials, both fiber manufacturability and transmission loss reduction can be achieved.

[0039] The average chlorine concentration in the first core can be below 1000 ppm. Under these conditions, the formation of matrix anomalies can be suppressed. Here, matrix anomalies refer to the crystallized portions of the glass, such as the core.

[0040] The average fluorine concentration in the first core can be below 5000 ppm. Under these conditions, the generation of abnormalities in the base material can be suppressed.

[0041] [Details of the embodiments disclosed herein]

[0042] The following description, with reference to the accompanying drawings, illustrates specific examples of the optical fiber and its parent material of this disclosure. It should be noted that the invention is not limited to these examples, but is defined by the claims, and is intended to include all modifications within the meaning and scope equivalent to the claims. In the description of the drawings, the same reference numerals are used to denote the same elements, and repeated descriptions are omitted.

[0043] Figure 1This is a cross-sectional view of the optical fiber according to the embodiment. The optical fiber 1 is made of silica-based glass. The optical fiber 1 has a core 10 and a cladding 20. The core 10 includes the central axis C of the optical fiber 1. The cladding 20 surrounds the core 10 and is externally connected to the core 10. The refractive index of the core 10 is greater than the refractive index of the cladding 20.

[0044] Core 10 has a first core 11 and a second core 12. The first core 11 includes a central axis C. The second core 12 surrounds the first core 11 and is externally connected to the first core 11. Cladding 20 has a first cladding and a second cladding (not shown). The first cladding surrounds the core 10 and is externally connected to the core 10. The second cladding surrounds the first cladding and is externally connected to the first cladding.

[0045] Core 10 contains chlorine, fluorine, and alkali metals. The average chlorine concentration of Core 11 is between 10 ppm and 500 ppm. The average chlorine concentration of Core 12 is between 500 ppm and 3000 ppm. The average chlorine concentration of Core 11 is lower than that of Core 12. The average fluorine concentration of Core 11 is between 500 ppm and 4000 ppm. The average fluorine concentration of Core 12 is between 500 ppm and 4000 ppm. The average fluorine concentration of Core 11 is higher than that of Core 12. The combined average chlorine and fluorine concentrations of Core 12 are less than 5000 ppm.

[0046] Core 10 contains alkali metal elements. The average concentration of alkali metal elements in Core 10 is between 0.2 ppm and 200 ppm. Core 10 contains any one of sodium, potassium, rubidium, cesium, and calcium as an alkali metal or alkaline earth metal element.

[0047] Optical fiber 1 is manufactured by drawing the optical fiber preform according to the embodiment. The optical fiber preform is made of silica-based glass. The optical fiber preform includes a core portion forming a core 10 and a cladding portion forming a cladding 20. The core portion includes the central axis of the optical fiber preform corresponding to the central axis C. The cladding portion surrounds the core portion and is externally connected to the core portion. The refractive index of the core portion is greater than the refractive index of the cladding portion.

[0048] The core comprises a first core 11 and a second core 12. The first core includes a central axis C. The second core surrounds and is externally connected to the first core. The cladding comprises a first cladding portion and a second cladding portion. The first cladding portion surrounds and is externally connected to the core. The second cladding portion surrounds and is externally connected to the first cladding portion. The type and concentration of dopants in the fiber matrix correspond to the type and concentration of dopants in fiber 1, therefore detailed descriptions are omitted. Alkali metal elements are added to the first core and diffused during fiber drawing.

[0049] Figure 2This is a flowchart illustrating a method for manufacturing an optical fiber according to an embodiment. It should be noted that an example of specific conditions is also described in the following description. The optical fiber 1 is manufactured sequentially through the following steps: preparation step S1, addition step S2, diameter reduction step S3, etching step S4, solidification step S5, first stretching and grinding step S6, first rod-in-collapse step S7, second stretching and grinding step S8, second rod-in-collapse step S9, OVD step S10, and drawing step S11. The method for manufacturing optical fiber 1 includes these steps S1 to S11. The method for manufacturing the optical fiber mother material includes these steps S1 to S10.

[0050] In preparation step S1, a first core tube and a second core tube are prepared. The first core tube is a glass tube made of silica-based glass, which becomes the first core 11 via a first core section. The first core tube is prepared as a glass tube for the diffusion of dopants such as alkali metal elements. The silica-based glass cylinder from which the first core tube originates contains chlorine at a concentration of 10 ppm to 500 ppm and fluorine at a concentration of 500 ppm to 4000 ppm. The concentration of other dopants and impurities is 10 ppm or less. The outer diameter of the first core tube is 30 mm to 40 mm. The inner diameter is 15 mm to 25 mm.

[0051] The method for determining chlorine concentration is as follows. The end face of optical fiber 1, perpendicular to the fiber axis (central axis C), is ground. The chlorine concentration is then determined at various locations along a straight line passing through the center on this end face using an electron beam microanalyzer (EPMA). The EPMA measurement conditions are, for example, an accelerating voltage of 20 kV, a probe electron beam diameter of less than 1 μm, and a measurement interval of less than 100 nm. The methods for determining the concentrations of other elements are the same.

[0052] The average mass fraction (average concentration) mentioned in this specification, for example, if it is the average fluorine concentration of a silica-based glass cylinder, is set as the concentration expressed by the following equation (1). F(r) represents the fluorine concentration at a position with radius r. c represents the radius of the silica-based glass cylinder. Similar to the case of fiber 1, the concentration is determined, for example, using EPMA, but the measurement conditions may differ from those of fiber 1. There is no problem as long as the concentration is calculated using the calibration curve under each condition.

[0053] [Mathematical Expression 1]

[0054]

[0055] The second core tube is a glass tube made of silica-based glass, which becomes the second core 12 via the second core section. The outer diameter of the second core tube is 40mm to 90mm. The inner diameter of the second core tube is 15mm to 30mm.

[0056] In this embodiment, the preparation step S1 is performed before the addition step S2, but the second core tube only needs to be prepared before the first insert collapse step S7. That is, the preparation step S1 includes the first core tube preparation step performed before the addition step S2 and the second core tube preparation step performed before the first insert collapse step S7.

[0057] In step S2, potassium (K) is added to the inner surface of the first core tube as a dopant of the alkali metal group. Potassium bromide (KBr) of 6g to 10g is used as the raw material. This raw material is heated to a temperature of 750°C to 850°C using an external heat source to generate raw material vapor. The raw material vapor, along with a carrier gas consisting of oxygen at a flow rate of 1 slm to 3 slm (equivalent to 1 liter / min to 3 liters / min under standard conditions), is introduced into the interior of the first core tube. Simultaneously, the first core tube is heated from the outside using an oxyhydrogen burner to raise the temperature of its outer surface to 1600°C to 1800°C. At this time, the burner is traversed at a speed of 30mm / min to 60mm / min for a total of 10 to 15 traverses to allow the K element to diffuse and be added to the inner surface of the first core tube.

[0058] In the diameter reduction process S3, the first core tube, to which K has been added, is reduced in diameter. At this time, oxygen flows inside the first core tube at a rate of 0.5 smol / L to 1.0 smol / L, while an external heat source heats the first core tube to a temperature of 2000°C to 2300°C on its outer surface. The external heat source is moved laterally a total of 6 to 10 times for heating, reducing the diameter of the first core tube until its inner diameter is 3 mm to 6 mm.

[0059] In etching step S4, the inner surface of the first core tube is etched. At this time, a mixed gas of SF6 (0.2 SLM to 0.4 SLM) and chlorine (0.5 SLM to 1.0 SLM) is introduced into the interior of the first core tube, while an external heat source heats the first core tube to perform vapor-phase etching. In this way, the inner surface of the first core tube, which contains a high concentration of impurities added along with the target dopant, can be removed, thereby eliminating these impurities.

[0060] In the solidification process S5, the first core tube is solidified. In S5, a mixed gas of oxygen (0.1 slm to 0.5 slm) and he (0.5 slm to 1.0 slm) is introduced into the interior of the first core tube, and the absolute pressure inside the first core tube is reduced to below 97 kPa. Simultaneously, the surface temperature is set to between 2000°C and 2300°C, thereby solidifying the first core tube. Through this solidification process, a first core (diameter 20 mm to 30 mm) is obtained.

[0061] In the first stretching and grinding process S6, the first core is stretched to make its diameter 20 mm or more and 30 mm or less, and the outer periphery of the first core is further ground to make its diameter 15 mm or more and 25 mm or less.

[0062] In the first insert collapse process S7, the first core obtained up to the first stretching and grinding process S6 is used as a rod, and the second core tube prepared in the preparation process S1 is used as a tube, and insert collapse is performed. According to this insert collapse method, the first core and the second core tube are heated by an external heat source and integrated. As a result, a second core is formed around the first core. Thus, a core (with a diameter of 20 mm to 90 mm) is obtained.

[0063] In the second stretching and grinding process S8, the core is stretched to make its diameter 20 mm or more and 35 mm or less, and the outer periphery of the core is further ground to make its diameter 15 mm or more and 25 mm or less.

[0064] In the second insert collapse process S9, the core obtained up to the second stretching and grinding process S8 is used as a rod, and a fluorinated silica-based glass tube is used as a tube, and insert collapse is performed. According to this insert collapse method, the core and the fluorinated silica-based glass tube are integrated by heating with an external heat source. As a result, a first cladding portion is formed around the core. The maximum relative refractive index difference between the core and the first cladding portion is approximately 0.34%. The synthesis result using this insert collapse method is that the amount of OH groups in the core and the adjacent first cladding portion can be suppressed to a sufficiently low level.

[0065] In the OVD process S10, firstly, a rod integrally formed from the core and the first cladding is stretched to a predetermined diameter. Next, a second cladding containing fluorine is synthesized on the outside of the rod, which has reached the predetermined diameter, using the OVD method. This produces the optical fiber preform.

[0066] In the fiber drawing process S11, optical fiber 1 is manufactured by drawing the optical fiber preform manufactured by the above-described optical fiber preform manufacturing method. The drawing speed is 1800 m / min to 2300 m / min. The drawing tension is, for example, 0.5 N.

[0067] Table 1 summarizes the specifications of seven types of optical fibers that were manufactured and evaluated. For each of fibers 1 to 7, the table shows the average K concentration of the core, the transmission loss at 1550 nm (α1.55), core diameter, cutoff wavelength (λcc), effective cross-sectional area (Aeff), average chlorine concentration of the first core, average chlorine concentration of the second core, average fluorine concentration of the first core, average fluorine concentration of the second core, the sum of the average chlorine and average fluorine concentrations of the second core, the average fluorine concentration of the cladding, and the difference between the average fluorine concentration of the cladding and the average fluorine concentration of the second core. Here, the cladding refers to the entire cladding including the first and second cladding layers. The various concentrations in this specification are not concentrations within the optical fiber, but rather concentrations within the glass tube that becomes the first and second cores after manufacturing. However, concentrations within the optical fiber can also be obtained. The boundary between the first and second cores in the optical fiber is defined as the point of greatest inclination between points in the radial direction of the chlorine concentration within the core. However, the concentrations are subject to noise according to the EPMA measurement conditions. In this case, a moving average of multiple points can be used to suppress the noise, and then the location of the boundary between the first and second cores can be calculated.

[0068] [Table 1]

[0069]

[0070] Figure 3 This is a graph showing the relationship between the combined average chlorine and fluorine concentrations of the second core and transmission loss. The horizontal axis represents the combined average chlorine and fluorine concentrations of the second core. The vertical axis represents the transmission loss at a wavelength of 1550 nm. When the combined value is below 1000 ppm, the transmission loss increases. This is believed to be because the viscosity of the second core increases due to the decrease in chlorine or fluorine concentration, leading to an increase in the density fluctuation component of Rayleigh scattering loss. On the other hand, when the combined value reaches around 5000 ppm, the transmission loss increases. This is believed to be because the increase in the concentration fluctuation component of Rayleigh scattering loss is greater than the decrease in the density fluctuation component caused by the decrease in viscosity due to the increase in chlorine or fluorine concentration.

[0071] Figure 4 This is a graph showing the relationship between the difference between the average fluorine concentration of the cladding and the average fluorine concentration of the second core, and the transmission loss. The horizontal axis represents the difference between the average fluorine concentration of the cladding and the average fluorine concentration of the second core. The vertical axis represents the transmission loss at a wavelength of 1550 nm. Figure 4 As shown, the greater the difference between the average fluorine concentration of the cladding and the average fluorine concentration of the second core, the lower the transmission loss. This is believed to be because the greater the difference in refractive index between the core and the cladding, the easier it is for the power distribution of light to concentrate on the core with lower Rayleigh scattering loss, even with the same effective cross-sectional area (Aeff).

[0072] Table 2 is a summary of the specifications of eight types of optical fibers that were manufactured and evaluated. In this table, for each of fibers 8 to 15, the average K concentration of the core, the transmission loss at 1550 nm (α1.55), core diameter, cutoff wavelength (λcc), effective cross-sectional area (Aeff), average chlorine concentration of the first core, average chlorine concentration of the second core, average fluorine concentration of the first core, and average fluorine concentration of the second core are shown.

[0073] [Table 2]

[0074]

[0075] Figure 5 This graph shows the relationship between the average chlorine concentration of the second core and the transmission loss. The horizontal axis represents the average chlorine concentration of the second core. The vertical axis represents the transmission loss at a wavelength of 1550 nm. When the average chlorine concentration of the second core is below 300 ppm, the transmission loss increases. This is believed to be because the glass defects cannot be repaired due to the lower chlorine concentration, resulting in increased transmission loss from the glass defects. On the other hand, when the average chlorine concentration of the second core reaches around 5000 ppm, the transmission loss increases. This is believed to be due to the increased concentration fluctuation component of Rayleigh scattering loss.

[0076] Table 3 is a summary of the specifications of eight types of optical fibers that were manufactured and evaluated. In this table, for each of fibers 16 to 23, the average K concentration of the core, the transmission loss at a wavelength of 1550 nm (α1.55), the core diameter, the cutoff wavelength (λcc), the effective cross-sectional area (Aeff), the average chlorine concentration of the first core, the average chlorine concentration of the second core, the average fluorine concentration of the first core, and the average fluorine concentration of the second core are shown.

[0077] [Table 3]

[0078]

[0079] Figure 6 This graph shows the relationship between the average potassium concentration of the core and the transmission loss. The horizontal axis represents the average potassium concentration of the core. The vertical axis represents the transmission loss at a wavelength of 1550 nm. As the average potassium concentration of the core decreases, the transmission loss deteriorates. This is believed to be because the density fluctuation component of Rayleigh scattering loss increases due to insufficient potassium concentration. On the other hand, when the average potassium concentration of the core reaches approximately 300 ppm, the transmission loss increases. This is believed to be due to the increased concentration fluctuation component of Rayleigh scattering loss.

[0080] Table 4 summarizes the specifications of six types of optical fibers that were manufactured and evaluated. In this table, for each of fibers 24 to 29, the following are shown: average K concentration of the core, transmission loss at 1550 nm (α1.55), core diameter, cutoff wavelength (λcc), effective cross-sectional area (Aeff), presence or absence of an OD substrate, average chlorine concentration of the first core, average chlorine concentration of the second core, average fluorine concentration of the first core, and average fluorine concentration of the second core.

[0081] [Table 4]

[0082]

[0083] For fibers 24 to 26, an exposure to a deuterium atmosphere (deuterium (D2) treatment) is performed after the drawing process S11. For fibers 27 to 29, no D2 treatment is performed. It has been confirmed that when the average chlorine concentration of the second core is below 300 ppm, an increase in transmission loss occurs. This is believed to be due to the formation of glass defects.

[0084] Table 5 summarizes the specifications of 13 types of fiber optic preforms that were manufactured and evaluated. For each preform (1 to 13), the table shows the average K concentration of the core, the average chlorine concentration of the first core, the average chlorine concentration of the second core, the average fluorine concentration of the first core, the average fluorine concentration of the second core, and the number of preform anomalies. Preform anomalies refer to portions of the glass, such as the core, that have crystallized. If sections with preform anomalies are drawn, the difference in thermal expansion coefficients between the glass and crystallized portions may lead to instability in fiber diameter. The number of preform anomalies is the number of anomaly sites contained in a single preform. The dimensions of all fiber optic preforms are identical across preforms 1 to 13.

[0085] [Table 5]

[0086]

[0087] When the average chlorine or fluorine concentration in the first core increases, the number of anomalies in the base material increases. It is believed that the anomalies in the base material are caused by the crystallization of compounds such as KCl or KF.

[0088] Explanation of symbols

[0089] 1… Optical fiber

[0090] 10…core

[0091] 11…First Chip

[0092] 12…Second Core

[0093] 20…cladding

[0094] C…Central axis

Claims

1. An optical fiber, composed of silica-based glass, comprising: core, and The cladding connected to the core, The refractive index of the core is greater than that of the cladding. The core has a first core including a central axis and a second core externally connected to the first core. The average mass fraction of chlorine in the first core is lower than the average mass fraction of chlorine in the second core. The average mass fraction of fluorine in the first core is higher than the average mass fraction of fluorine in the second core. The combined average mass fraction of chlorine and fluorine in the second core is below 5000 ppm. The core contains any one or both of alkali metals and alkaline earth metals. The difference between the average mass fraction of fluorine in the cladding and the average mass fraction of fluorine in the second core is between 8400 ppm and 9000 ppm.

2. The optical fiber according to claim 1, wherein, The average mass fraction of chlorine in the first core is between 10 ppm and 500 ppm.

3. The optical fiber according to claim 1 or claim 2, wherein, The average mass fraction of chlorine in the second core is between 500 ppm and 3000 ppm.

4. The optical fiber according to any one of claims 1 to 3, wherein, The average mass fraction of fluorine in the first core is between 500 ppm and 4000 ppm.

5. The optical fiber according to any one of claims 1 to 4, wherein, The average mass fraction of fluorine in the second core is between 500 ppm and 4000 ppm.

6. The optical fiber according to any one of claims 1 to 5, wherein, The average total mass fraction of alkali metals and alkaline earth metals in the core is between 0.2 ppm and 200 ppm.

7. The optical fiber according to claim 6, wherein, The average combined mass fraction of alkali metals and alkaline earth metals in the core is above 30 ppm.

8. The optical fiber according to any one of claims 1 to 7, wherein, The core contains any one of sodium, potassium, rubidium, cesium, and calcium as an alkali metal element or an alkaline earth metal element.

9. The optical fiber according to any one of claims 1 to 8, wherein, The optical fiber does not have an OD base.

10. The optical fiber according to any one of claims 1 to 9, wherein, The difference between the average mass fraction of fluorine in the cladding and the average mass fraction of fluorine in the second core is between 8600 ppm and 9000 ppm.

11. The optical fiber according to any one of claims 1 to 10, wherein, The average mass fraction of fluorine in the coating is between 8000 ppm and 13000 ppm.

12. An optical fiber preform, composed of silica-based glass, possessing: core, and The cladding portion connected to the core portion, The refractive index of the core is greater than that of the cladding. The core has a first core including a central axis and a second core connected to the outside of the first core. The average mass fraction of chlorine in the first core is lower than the average mass fraction of chlorine in the second core. The average mass fraction of fluorine in the first core is higher than the average mass fraction of fluorine in the second core. The combined average mass fraction of chlorine and fluorine in the second core is less than 5000 ppm. The core contains any one or both of alkali metal elements and alkaline earth metal elements. The difference between the average mass fraction of fluorine in the cladding portion and the average mass fraction of fluorine in the second core portion is between 8400 ppm and 9000 ppm.

13. The optical fiber mother material according to claim 12, wherein, The average mass fraction of chlorine in the first core is less than 1000 ppm.

14. The optical fiber mother material according to claim 12 or claim 13, wherein, The average mass fraction of fluorine in the first core is less than 5000 ppm.

Citation Information

Patent Citations

  • Optical fiber containing alkali metal oxide

    JP2009541796A

  • Optical fiber

    JP2017076053A

  • Optical fiber

    JP2019191297A

  • Information processing device, information processing method, and program

    JP2021117840A

  • Optical fiber containing an alkali metal oxide and methods and apparatus for manufacturing same

    CN1842499A